(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The problem of studying architectural decor of Central Asia in the history of development of architecture from ancient times to the present acquires a special urgency in the light of scientific substantiation of application of architectural decor elements on facades, in interiors of buildings and constructions, and ways of formation of its structure, tendencies of creation of certain art images influencing psyche of people on their consciousness.